2000
DOI: 10.1007/pl00011175
|View full text |Cite
|
Sign up to set email alerts
|

Haematogenous Vertebral Osteomyelitis in the Elderly

Abstract: The aim of our study was to analyse the characteristics of haematogenous vertebral osteomyelitis (HVO) in the elderly. A retrospective comparative analysis of the medical records of 72 patients (38 younger than 63 years, group 1, and 34 aged 63 years and over, group 2) with haematogenous vertebral osteomyelitis of confirmed aetiology was carried out. Intravenous drug addiction and infection with the human immunodeficiency virus were seen in 4/38 (10%) and 5/38 (13%) patients from group 1 and 0/34 patients (0%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 17 publications
1
17
1
2
Order By: Relevance
“…The onset of the symptom is often insidious and could easily be underestimated (or ignored) by both patients and doctors. Patients could present a great diversity of pathologic features, clinical manifestations, and various complications [7,26,46]. The most common symptom is axial pain; it may be insidious in onset during the early stages of infection but typically worsen at the advanced stage.…”
Section: Clinical Presentations and Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…The onset of the symptom is often insidious and could easily be underestimated (or ignored) by both patients and doctors. Patients could present a great diversity of pathologic features, clinical manifestations, and various complications [7,26,46]. The most common symptom is axial pain; it may be insidious in onset during the early stages of infection but typically worsen at the advanced stage.…”
Section: Clinical Presentations and Evaluationmentioning
confidence: 99%
“…It has been extensively reported that the most common causative pathogen is Staphylococcus aureus (S. aureus), followed in frequency by Streptococcus species, Escherichia coli, Staphylococcus epidermis, Aeruginosus Bacillus and Pseudomonas [7,8,17,19,31,35,36,47,52,56,64,71]. A large scale study singled out S. aureus as the most common infective agent with a frequency as high as 48% (123/255).…”
Section: Microbiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Spondylodiszitis weiterhin eine Herausforderung dar. Ihre Inzidenz beträgt etwa 2,2:100.000, wobei in den letzten Jahren eine Zunahme zu verzeichnen war, welche auf die zunehmend ältere Bevölkerung mit der daraus resultierenden Multimorbidität sowie auf verbesserte diagnostische Möglichkeiten mit einer höheren Spezifität zurückgeführt werden kann [1]. Am häufigsten betroffen ist die lumbale Wirbelsäule [7].…”
Section: Diskussionunclassified